Поняття санкції статті (санкції частини статті) особливої частини Кримінального Кодексу України - Перепелиця, А.І.; Назимко, Є.С. (Часопис Київського університету права, 2009)
В статье изложена авторская позиция понятия санкции статьи (санкции части статьи) Особенной части Уголовного кодекса Украины. Анализируется понятия правовой нормы, санкции правовой нормы, уголовно-правовой санкции, санкции статьи Уголовного кодекса. Приводятся аргументы в пользу разграничения категорий уголовного права и уголовного законодательства. Need of accenting attention on given problem is conditioned that use term and notion, not installed in legislation, contributes the certain mess of the understanding the phenomenas and processes, which adjusts the law. Main trends legal political state are considered in article in sphere of the reluctance to criminality and is installed amongst them place penal politicians’ state.